Her first mistake - Elliot, Kendra (Noelle Marshall, 2025)
Thirteen years ago, Assemblyman Derrick Bell was murdered in his home by an intruder. His wife, Noelle Marshall, was left for dead. The crime was unsolved, but it wasn't forgotten. Today the FBI is tackling a fresh perspective on the case and looking to Noelle, now a detective for the Deschutes County sheriff's office, for new clues. It is reopening everything Noelle thought was behind her. Memories of her escape from a traumatic childhood. A marriage that wasn't the perfect love story she'd been promised. And a husband whose charm and privilege hid a dark side. But Noelle has been hiding something too: a secret about the night Derrick died that she has never told anyone. As past and present and leads and misleads collide, one thing is frighteningly clear. Derrick's murder wasn't just unsolved. It's unfinished. And only the truth--no matter the risk--can save the next victim.